Skeletal bone density is associated with periodontitis: systematic review and metanalysis - Kloeckner, Fernando; Barros, Otto Ferraz Fernandes; Uliana, Jaíne Cocco; Kantorski, Karla Zanini (Brazilian Dental Science, 2024)
Objective: This study aimed to evaluate whether low skeletal bone density conditions, such as osteoporosis (OPR), osteopenia (OPN) and low bone mineral density (low BMD) are associated with periodontitis. Material and Methods: Embase, Lilacs, PubMed, Scopus, Web of Science, Livivo and Google Scholar were searched up to July 2023. Observational studies comparing different BMD levels, showing clinical data of periodontitis and with adjusted analysis for confounding factors were included. Reviewers independently conducted study selection, data extraction, methodological quality and certainty of evidence assessments. Results: 32 studies were included, 20 eligible for the metanalysis. Subjects with OPR/OPN/lowBMD show significantly more odds of having periodontitis (OR=1.40, 95%CI=1.26-1.53, I2=82.9%). Association between skeletal bone density and periodontitis showed dose-response gradient, with higher effect size in osteoporotic when compared to the osteopenic subjects. Statistical association with low heterogeneity was observed in female (OR=1.42, 95%CI=1.13-1.71, I2=20.4%), in post-menopausal women (OR=1.47, 95%CI=1.15-1.78, I2=18.7%) and periodontitis case-definition based in clinical attachment level/alveolar bone loss (OR=1.39, 95%CI 1.16-1.62, I2=26.5%). Conclusion: Routine periodontal supportive care and screening for skeletal bone diseases risk groups, may be an important tool to fully assess and care for patients with osteoporosis and osteopenia. KEYWORDS Metanalysis; Osteopenia; Osteoporosis; Periodontal attachment loss; Periodontitis.